Evaluasi Kapasitas Hidraulik Saluran Irigasi Menggunakan Metode Manning - Siti Ulpah Nurazizah; Sulwan Permana; Dendi Yogaswara (Jurnal Konstruksi, 2026)
Garut Regency is one of the regions in West Java Province with significant potential in the agricultural sector. One of the key infrastructures supporting these activities is the Cimaragas Irrigation Canal, located in Karangpawitan District. In recent years, this area has frequently experienced flooding due to overtopping of the irrigation canal, which is no longer capable of conveying the flow discharge, particularly during the rainy season. In addition, siltation and the accumulation of sediment and solid waste have further exacerbated the reduction in channel capacity. This study aims to assess water demand and water availability within the Cimaragas irrigation system, as well as to determine the ideal dimensions of the irrigation canal capable of conveying the planned discharge. The research employs a quantitative and descriptive approach, with hydrological and hydraulic analyses using the Manning equation and a trial-and-error method to determine the optimal cross-sectional dimensions. The analysis results indicate that the highest water demand occurs in April, amounting to 413.90 L/s, while the highest water availability also occurs in the same month at 639 L/s, indicating that the study area generally experiences a water surplus. Based on the capacity analysis of a trapezoidal channel section, the optimal dimensions obtained are a bottom width (b) of 5 m, a flow depth (y) of 1.8 m, a side slope (x) of 1.5, and a channel bed slope (S) of 0.005, resulting in an actual discharge of 254.285 L/s, which closely matches the irrigation discharge requirement of 245 L/s. From these results, it can be concluded that the existing irrigation canal is no longer adequate to convey the actual discharge, and therefore improvements and dimensional modifications are required by the Government of Garut Regency. This study provides technical recommendations for increasing the capacity and efficiency of the irrigation network to support the sustainability of the agricultural sector. The findings may serve as a basis for planning canal rehabilitation by local authorities to minimize flood risk and optimize irrigation water distribution.